Pregnangy Toxemia of Sheep - ΣΕΙΤΑΡΙΔΗΣ Κ.; ΤΣΕΒΑΣ Ι.; ΠΑΠΑΔΟΠΟΥΛΟΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The clinical symptoms, the anatomopathological lesions and the results of the treatment with glucose and methionine intravenously and sodium propionate per os of 13 pregnancy toxemia cases in ewes are described. The ewes were pregnant (3 last weeks of pregnancy), they carrying 2-4 embryos, they were in good nutritional condition and were belonging in house breedings. Nine out of thirteen ewes, which received the above treatment (69,2%) died and 4(30,8%) survived.